2014
DOI: 10.5194/nhess-14-1965-2014
|View full text |Cite
|
Sign up to set email alerts
|

MEDEX: a general overview

Abstract: Abstract. The general objective of the international MEDiterranean EXperiment (MEDEX) was the better understanding and forecasting of cyclones that produce high impact weather in the Mediterranean. This paper reviews the motivation and foundation of MEDEX, the gestation, history and organisation of the project, as well as the main products and scientific achievements obtained from it. MEDEX obtained the approval of World Meteorological Organisation (WMO) and can be considered as framed within other WMO actions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 113 publications
1
69
0
3
Order By: Relevance
“…It is a cyclone that forms or intensifies from a pre-existing cyclone to the south of the Alps for orographic effect (Jansà, 1997;Jansa et al, 2014) over the Gulf of Genoa, Ligurian Sea. This cyclone generally remains stationary but sometimes can determine the weather of central Europe (Sáez de Cámara et al, 2011) or the Italian peninsula (Trigo et al, 1999) according to the "Vb" and "Vd" Van Bebber cyclone tracks (Bartholy et al, 2006).…”
Section: Geographical Features Of Genoamentioning
confidence: 99%
“…It is a cyclone that forms or intensifies from a pre-existing cyclone to the south of the Alps for orographic effect (Jansà, 1997;Jansa et al, 2014) over the Gulf of Genoa, Ligurian Sea. This cyclone generally remains stationary but sometimes can determine the weather of central Europe (Sáez de Cámara et al, 2011) or the Italian peninsula (Trigo et al, 1999) according to the "Vb" and "Vd" Van Bebber cyclone tracks (Bartholy et al, 2006).…”
Section: Geographical Features Of Genoamentioning
confidence: 99%
“…6 shows that autumn was the season with the highest frequency of flash flood events, as well as with the highest number of fire service operations, followed by winter. Autumn in Greece is actually the season with the highest frequency of rainfall and the highest accumulated rainfall, particularly in what concerns the mainland (Jansa et al, 2014;Lagouvardos and Kotroni, 2007;Kotroni et al, 1999; 1996). This is in accordance with previous analysis of historical floods in Greece, which concluded that autumn was the season with the richest flood record for the period 1880-2010 .…”
Section: Relation Between Hazard and Impact Indicatorsmentioning
confidence: 99%
“…For this reason, gaining insights into the synoptic climatology of cyclones for the whole MB (i.e., seasonal frequency, spatial distribution and regions favoring cyclogenesis) is important. A significant contribution to this task is the comprehensive paper (Campins et al, 2011) and the MEDEX database as part of the MEDEX program (Jansa et al, 2014).…”
Section: Synoptic Circulation Patterns That Induce Heavy Rainmentioning
confidence: 99%